Ultra-rapid lispro or fast-acting aspart compared to standard insulin lispro and aspart using closed-loop insulin therapy: a systematic review and meta-analysis of randomized control trials - Rakab, Mohamed Saad; Rateb, Rahma Mogahed; Elsalakawi, Basel Hatem; Al Zoubi, Bashar M.; Nazir, Abubakar; Abu-Laila, Mutaz Moath; Ghanem, Abdelrahman Sherif; Maamoun, Alaa; Mattar, Mohab; Ataallah, Basma; Layden, Brian T.; Mahmoud, Abeer M. (Frontiers in Endocrinology, 2025)
BackgroundUltra-rapid-acting insulin (URAI) improves glycemic control by reducing variability; however, optimal strategies for its use, especially within hybrid closed-loop (HCL) insulin delivery systems, remain unclear. This meta-analysis assesses the efficacy and safety of combining URAI with HCL systems in maintaining the euglycemic range and reducing glycemic excursions.MethodsWe systematically searched PubMed, Scopus, Cochrane Library, Web of Science, and related article citations for relevant studies. Outcomes assessed included time in range (TIR), time below range (TBR), and time above range (TAR) during overall 24-hour periods, daytime, nighttime, postprandial, and post-exercise periods, as well as adverse events. Dichotomous outcomes were summarized using risk ratios (RR), and continuous outcomes were pooled using mean differences (MD) presented with 95% confidence intervals (CI).ResultsURAI showed a modest, statistically non-significant improvement in TIR (70–180 mg/dL) compared to standard insulin (MD 0.87%, 95% CI [-0.21 to 1.85], P = 0.12). Importantly, glycemic variability significantly improved with URAI, as demonstrated by reductions in the coefficient of variation (CV) (MD -0.78%, 95% CI [-1.44 to -0.12], P = 0.02). The combination of URAI with HCL systems significantly reduced hypoglycemia (TBR <70 mg/dL: MD -0.32%, 95% CI [-0.56 to -0.13], P = 0.002). However, overall reductions in TAR >250 mg/dL and TAR >180 mg/dL were statistically non-significant.ConclusionThe integration of URAI with HCL demonstrates encouraging improvements in glycemic outcomes, notably reduced glucose variability and nighttime hypoglycemia risk. However, further research with larger sample sizes is essential to confirm these benefits and establish broader clinical recommendations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024594375, identifier CRD42024594375.